An extended laser cavity centered at 780 nm for high-resolution laser spectroscopy applications. (1st May 2023) - Álvarez, J; Pimienta, J; Mercado, E; Sarmiento, R
Abstract: Laser diodes (LDs) working in free mode present different types of effects such as shift and broadening of the spectral peak, determined by external factors such as temperature, electric current or mechanical vibrations, which are undesirable when required in applications such as high resolution laser spectroscopy, metrology or laser cooling. To reduce the width of the spectral emission peak of a laser, different configurations or optical setups are used, among which one of the most effective is to extend the optical resonator of the LD and use optical feedback, either with the help of a partially reflective mirror or with a diffraction grating. In this work, we present the design, construction, and characterization of a compact extended-cavity diode laser (ECDL) in Littrow configuration. The ECDL was machined on an aluminum block using computerized numerical control. It operates at a wavelength of 780.24 nm with a maximum output power of 35 mW. The results showed a spectral linewidth of 340 kHz using the self-heterodyne technique and a frequency stability of 0.47 MHz when the cavity was stabilized with an atomic reference.